Personality-guided behavior therapy - Farmer, Richard F. (Personality-guided psychology / series editor Theodore Millon, 2005)
(from the foreword) It is toward the end of alerting psychologists who work in diverse areas of study and practice that the present series, entitled "Personality-Guided Psychology", has been developed for publication by the American Psychological Association. The originating concept underlying the series may be traced to Henry Murray's seminal proposal in his 1938 volume, "Explorations in Personality", in which he advanced a new field of study termed personology. It took its contemporary form in a work of the series editor, Theodore Millon, PhD, DSc, published in 1999 under the title "Personality-Guided Therapy". This portion of the Series, as its title indicates, addresses the use of personality-guided behavior therapy.